3.3: New Electron Transporting Materials for Long‐lifetime Fluorescent Blue OLED Devices. (28th November 2018) - Huang, Heh-Lung; Guo, Huang-Ming; Lai, Cheng-Chang; Lin, Chi-Jen; Chang, Min-Jong
Abstract : A series of new electron transporting materials with deep HOMO levels were designed and developed. The HOMO levels were all above 6.3 eV. The fluorescent blue devices exhibited high current efficiency of 9.1–10.9 cd/A, high EQE of 8.0–9.4%, and the LT95 lifetime is more than 250 h under 1000 cd/m 2 .